Peran Pemahaman Amanat Agung dalam Meningkatkan Pelaksanaan Misi di GSJA Gunungsari Balikpapan - Melissa Krisharmoni , Febe; Oscar Lontoh , Frederich (Jurnal Teologi dan Pelayanan Kerusso, 2025)
This The Great Commission, as stated in Matthew 28:19–20, is a universal calling for every believer to proclaim the Gospel and make disciples of all nations. However, in the context of GSJA Gunungsari Balikpapan, it has been found that a low level of understanding of the Great Commission may pose a potential obstacle to the effective execution of mission work. This research employs a quantitative approach using a descriptive survey design and regression analysis to measure the impact of congregational understanding on mission implementation. Data were collected through questionnaires distributed to members of GSJA Gunungsari Balikpapan and were subsequently analyzed to determine the correlation between the understanding of the Great Commission and participation in church missions. The findings reveal a significant positive influence between the level of understanding of the Great Commission and congregational involvement in mission activities, with a considerable percentage of contribution. This study is expected to provide valuable insights for GSJA Gunungsari Balikpapan in strengthening its spiritual development strategies to enhance both the understanding and participation of its members in church missions.